Minimising the limitations of using dietary analysis to assess foodweb changes by combining multiple techniques. (November 2018) - Horswill, C.; Jackson, J.A.; Medeiros, R.; Nowell, R.W.; Trathan, P.N.; O'Connell, T.C.
Highlights: The limitations of diet analyses can be minimised by combining multiple techniques. Stable isotope analysis can be used to detect subtle changes in diet composition. DNA analysis of faeces offers a high resolution snap-shot of target prey species. These samples can be collected more regularly than samples of stomach contents. Combining these methods provides more data for assessing ecosystem status from diet. Abstract: Dietary studies of marine predators offer an immediate signal of foodweb changes occurring at lower trophic levels, and therefore are often used to assess the ecosystem status of marine systems. Conventionally, these studies are based on morphological analysis of prey remains in stomach contents, involving invasive and destructive techniques to collect samples. More recently, the number of dietary studies based on less invasive biochemical and molecular approaches has dramatically increased. However, all three methods, morphological, biochemical and molecular, have well-documented limitations for resolving taxonomy, temporal variation or biomass composition. In this study, we minimise these limitations by considering multiple techniques in combination. As a case study, we report the target prey species and diet composition of a marine predator that has been used to assess annual change in managed fishing areas for several decades, the macaroni penguin Eudyptes chrysolophus . We use biochemical (stable isotope) and molecular (DNA) analysis of faecal samples collected across the different phases of a single breeding season, and compare the resolved diet to a 26-year dataset of stomach contents collected from a closely located colony (0.25 km apart) that exploits identical foraging grounds. Molecular analysis increased the known target prey species for this highly monitored population by 31%, including a fish species of commercial importance. Biochemical analysis detected subtle changes in the proportion of fish and krill in the diet, demonstrating promising opportunities for using a combined molecular and biochemical method to assess inter-annual foodweb changes at lower trophic levels. The combined approach offers a less invasive sampling methodology, compared to morphological analysis, and provides more information regarding prey species diversity and the overall trophic signature of the diet. Further studies are required to examine the feasibility of using this approach for long-term dietary studies of different marine predator species.